2015
DOI: 10.1016/j.ejphar.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Role and therapeutic potential of G-protein coupled receptors in breast cancer progression and metastases

Abstract: G-protein-coupled receptors (GPCRs) comprise a large family of cell-surface receptors, which have recently emerged as key players in tumorigenesis, angiogenesis and metastasis. In this review, we discussed our current understanding of the many roles played by GPCRs in general, and particularly Angiotensin II type I receptor (AGTR1), a member of the seven-transmembrane-spanning G-protein coupled receptor superfamily, and its significance in breast cancer progression and metastasis. We have also discussed differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…Given the appreciation of their role in cancer, the importance of GPCRs for anticancer drug discovery is undisputable, although very few members have been exploited in pursuit of anticancer therapies. In this study, we have confirmed the clinical value of GPSM2.Thus, GPSM2 may be a promising target for new cancer therapy through regulating GPCRs pathway (6,30). Due the value of GPSM2 in predicting disease recurrence, it would be better to add GPMS2 to the NGS panels like Oncotype Dx (31).…”
Section: Discussionsupporting
confidence: 65%
“…Given the appreciation of their role in cancer, the importance of GPCRs for anticancer drug discovery is undisputable, although very few members have been exploited in pursuit of anticancer therapies. In this study, we have confirmed the clinical value of GPSM2.Thus, GPSM2 may be a promising target for new cancer therapy through regulating GPCRs pathway (6,30). Due the value of GPSM2 in predicting disease recurrence, it would be better to add GPMS2 to the NGS panels like Oncotype Dx (31).…”
Section: Discussionsupporting
confidence: 65%
“…Signaling pathways have been previously shown to be highly interconnected, with multiple points of convergence, cross talk and feedback loops, and these pathways can activate or inhibit each other, depending on the context and on cellular conditions (32)(33)(34)(35)(36). A compensatory mechanism, due to the presence of other signaling pathways, could explain the absence of or decrease in the expression of phosphoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant cancer cells are known to hijack the normal physiological functions of GPCRs to survive, proliferate autonomously, evade the immune system, increase blood supply, invade their surrounding tissues and disseminate to other organs. Increased GPCR expression has been observed in various cancers including breast cancer [ 23 ]. Herein we observe an overall increase in percentage of GPCRs from 7% of total proteins identified in HOS cells to 18% of total in the human metastatic143B cells (Fig CA in S1 File ).…”
Section: Resultsmentioning
confidence: 99%